Development of ultra high strength concrete based on locally available materials and fly ash - Chung, Mui Zhi (Universiti Malaysia Sarawak, UNIMAS, 2010)
Ultra High Strength Concrete (UHSC) is a concrete with a very high strength, high durability, large elastic modulus and very densed structure. It is widely used in construction of skyscrapers such as Petronas Twin Tower, Shawnessy Light Rail Transit (LRT) Station and Seonyu footbridge. The concrete with very high strength has low water binder ratio, high cement content mixed with chemical product such as fly ash, optimum aggregates size and addition of superplasticizer. This thesis presents the results of an experimental study on the ultra high strength concrete using local available materials. This study focuses on the fresh and hardened properties of concrete which are slump, flow, compressive strength and flexural tensile strength of the concrete containing different percentages of fly ash, water binder ratio and superplasticizer dosage. The properties of aggregates, cement and fly ash were also determined. The cement was replaced with 0%, 15%, 20% and 25% of fly ash. The hardened concrete properties were tested at the ages of 28 and 56 days. Results show that the workability, compressive strength and flexural tensile strength increase with the increase in percentage of replacement of fly ash for the concrete. The concrete with water binder ratio of 0.24, 20% of fly ash replacement and 3% superplasticizer has highest compressive and flexural tensile strength at 56 days, which are 114.5 MPa and 13.30 MPa respectively.